Study of the biological effect of oligochitosan prepared by γ-CO-60 irradiation method on Spirulina platensis - Luân, Lê Quang; Xô, Dương Hoa (Vietnam Journal of Biotechnology, 2016)
Chitosan with initial molecular weight (Mw) about 193 kDa and the deacetylation degree of about 80% was irradiated by gamma rays from a Co-60 source in powder state for degradation. The results on Mw estimation by gel permeation chromatography method indicated that oligochitosan products with Mw from 3.7 to 28.9 kDa were successfully prepared by irradiation of chitosan samples at doses from 300 to 2000 kGy. The prepared oligochitosans were then supplemented into the cultivated media for investigation of the biological effect on the cyanobacteria (blue – green alga) namely Spilurina platensis. The obtained results indicated that all of radiation degraded chitosan samples showed a growth promotion effect on the enhancement of fresh and dried biomass S. platensis after 7 days supplementation. The oligochitosan product with Mw ~ 15,4 kDa obtained from the irradiation dose of 500 kGy displayed the best growth promotion effect for the tested alga and the optimum concentration for supplementation of this product was found at 100 ppm. In addition, The supplementation with 100 ppm of the oligochitosan product enhanced 49.5% the fresh biomass and 59.1% the dried biomass of the tested alga after 7 days cultivating. The addition of oligochitosan also increased the dried matter, protein, carbohydrate and lipid contents of the harvested alga product in 7.0, 23.3, 27.3 and 37.5%, respectively. It can be seen that the oligochitosan product prepared from natural organic compound by gamma Co-60 irradiation method promised to be potential used as a safe and highly effective growth promoter for alga to biomass production of S. platensis.